Problems of the socioeconomic development of the border territory of the countries of Northeast Asia and their influence on the international integration of peripherals - Volynchuk, Andrey B.; Pestsov, Sergey K. (Cuestiones Políticas, 2020)
The article studies the problems of the socioeconomic development of the border territory of the countries of Northeast Asia (NEA) and its influence on the international integration of peripherals in Asia. The study starts from the assumption that the international integration of border areas depends on the presence of certain factors in the development of these territories. At a methodological level, various tools of geopolitical and geostrategic analysis were used in the coordinates of interdisciplinary dialogue, also using theoretical and methodological devices from various disciplines such as: the humanities, international relations, economics, and socioeconomic geography. The discrepancy between the national average development indicators is typical of the border periphery of all Northeast Asian countries. The findings obtained allow us to conclude that the territorial disparities revealed in the course of the study are manifested in all areas of social relations (demography, economy, management, infrastructure). Despite the peripheral / border areas function in different natural, economic, and political conditions and have different traditions of economic development. However, the structure of development problems, in general, has similar mechanisms of influence in the processes of economic integration in this region of the world.